Optically resolving the dynamic walking of a plasmonic walker couple - Urban, Maximilian J.; Zhou, Chao; Duan, Xiaoyang; Liu, Na (Nano letters, 2015)
Deterministic placement and dynamic manipulation of individual plasmonic nanoparticles with nanoscale precision feature an important step toward active nanoplasmonic devices with prescribed levels of performance and functionalities at optical frequencies. In this Letter, we demonstrate a plasmonic walker couple system, in which two gold nanorod walkers can independently or simultaneously perform stepwise walking powered by DNA hybridization along the same DNA origami track. We utilize optical spectroscopy to resolve such dynamic walking with nanoscale steps well below the optical diffraction limit. We also show that the number of walkers and the optical response of the system can be correlated. Our studies exemplify the power of plasmonics, when integrated with DNA nanotechnology for realization of advanced artificial nanomachinery with tailored optical functionalities.
Gesehen am 07.07.2020